Analysis of DNA methylation and TP53 mutational status for differentiating feline oral squamous cell carcinoma from non‐neoplastic mucosa: A preliminary study. (18th July 2020) - Renzi, Andrea; Morandi, Luca; Lenzi, Jacopo; Rigillo, Antonella; Bettini, Giuliano; Bellei, Emma; Giacomini, Alessandra; Tinto, Debora; Sabattini, Silvia
Abstract: Feline oral squamous cell carcinoma (FOSCC) is characterized by high local invasiveness and early bone lysis. The late diagnosis largely limits the efficacy of therapy and increases treatment‐related morbidity. The aim of this exploratory study was to assess the methylation pattern of 10 candidate genes and TP53 mutational status in histologic samples of FOSCC. Results were compared with normal oral mucosa and oral inflammatory lesions, in order to establish a gene panel for FOSCC detection. For 10 cats, the above analyses were also performed on oral brushing samples, in order to explore the utility of these methods for screening purposes. Thirty‐one FOSCC, 25 chronic inflammatory lesions and 12 controls were included. TP53 mutations were significantly more frequent in the FOSCC (68%) than in the non‐neoplastic oral mucosa (3%; P <.001). Based on lasso regression analysis, a step‐wise algorithm including TP53, FLI1, MiR124‐1, KIF1A and MAGEC2 was proposed. The algorithm allowed to differentiate FOSCC with 94% sensitivity and 100% specificity (accuracy, 97%). When applying the proposed algorithm on 10 brushing samples, accuracy decreased to 80%. These results indicate that the altered DNA methylation of specific genes is present in FOSCC, together with a significant proportion of TP53 mutations. Such alterations are infrequent in normal oral mucosa and chronic stomatitis in cats, suggesting their involvement in feline oral carcinogenesis and their utility as diagnostic biomarkers. Further studies on a high number of brushing samples will be needed to assess the utility of a screening test for the early detection of FOSCC.